2009
DOI: 10.1159/000265942
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Group B Streptococcus Screening in Pregnancy: A Systematic Review

Abstract: Background: Group B streptococcus (GBS) is an important cause of neonatal sepsis. Guidelines advise to collect cultures at 35–37 weeks’ gestation and to administer intrapartum antibiotic prophylaxis in case of GBS-positive cultures, as well as in all preterm deliveries. Improved effectiveness of antenatal cultures might help to further decrease GBS early-onset disease. Objective: To determine the best timing of antenatal cultures, which may help establish optimal prevention of perinatal GBS infection in both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
4
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 103 publications
3
41
4
2
Order By: Relevance
“…Although a great heterogeneity of PPVs has been described [5,6,9] ranging (43-100%), our study revealed a considerably low PPV of 24.4%. This weak concordance between prenatal and intrapartum culture results could be attributed to several variables, namely (1) timing of prenatal GBS screening; (2) laboratory methodologies; and (3) antibiotic usage.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Although a great heterogeneity of PPVs has been described [5,6,9] ranging (43-100%), our study revealed a considerably low PPV of 24.4%. This weak concordance between prenatal and intrapartum culture results could be attributed to several variables, namely (1) timing of prenatal GBS screening; (2) laboratory methodologies; and (3) antibiotic usage.…”
Section: Discussioncontrasting
confidence: 67%
“…The influence of the timing of prenatal GBS screening in this study would be neglectable; in fact, all enrolled GBS positive women were screened at 35-37 weeks of gestation, which has been considered ideal for correlating with GBS colonization status at delivery, by longitudinal studies [9].…”
Section: Discussionmentioning
confidence: 99%
“…However the expected predictive values were too optimistic. In studies evaluating antenatal culture to predict intrapartum status for genital colonization with GBS, reported sensitivities range from 51% to 87%, specificities from 93.7% to 97.1%, positive and negative predictive values from 60.6% to 87% and from 88% to 96% [77,[79][80][81][82][83][84][85][86][87].…”
Section: Timing Of Screeningmentioning
confidence: 99%
“…However, it should not be forgotten that there have been reports on declining amount of studies towards detection of GBS carriers between 35 and 37 weeks of gestation. It has been shown that at this stage, about 6% pregnant women colonized by GBS had negative results of GBS cultures [17]. In 2010, Berardi et al published a study where they found that the majority of cases of early-onset GBS infection among newborns in years 2003-2008 were related to mothers who had a negative screening result for S. agalactiae.…”
Section: Newborn Infections and Prophylaxismentioning
confidence: 99%
“…Wykazano bowiem, że na tym etapie ciąży około 6% skolonizowanych GBS ciężarnych posiada ujemne wyniki posiewów w kierunku GBS [17]. Również w 2010 roku Berardi i wsp.…”
unclassified